Regional Economic Outlook, October 2009, Western Hemisphere : Crisis Averted: What's Next?. (Regional Economic Outlook, 2009)
The impact of the global financial crisis and recession on the Latin America and Caribbean region was substantial, but the worst is over for most countries. The region avoided falling into a crisis of its own, performing relatively well amid strong external shocks. Many countries have now returned to growth. The region now faces the challenge of adapting to a new global environment that will not be as favorable as in the past. The latest edition of the report explores the lessons and policy agenda emerging from the recent performance of the Latin America and Caribbean region, drawing also on the broader international experience. Published biannually in May and October.